Idhmaju Taqyiimi al-Ashili Fi Ta‘allumi Lughotil ‘Arabiyyat: al-Mandzuratu Nadzoriyyat Wal-Athari Ghoir al-Ikhtibariyyah: Integration of Authentic Assessment in Arabic Language Learning: Theoretical Perspectives and Non-Test Implications - Luqi Fauziyah; Dewi Nur Masitho; M. Baihaqi; Nila Sari Syafitri; Hasanah Dwi Yusuf (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2025)
Authentic assessment is an evaluation approach that focuses on students’ ability to perform tasks with real-world relevance. In Arabic language education, authentic assessment is a primary tool to evaluate cognitive, affective, and psychomotor competencies. This study examines the types of authentic assessment, their implementation, and the challenges associated with authentic assessment in Arabic language instruction at the school level. The research used a qualitative library methodology. Data analysis included three stages: reduction, presentation, and conclusion. Results show that authentic assessment includes performance assessment, portfolios, projects, and self-assessment. Using authentic assessment increases students' motivation and enhances their competence in communicating in Arabic. However, barriers remain. Time constraints, lack of teacher preparation, and difficulties in developing assessment rubrics hinder effective assessment. Comprehensive teacher training and strong institutional policies are needed to address these challenges. This research aims to improve Arabic language instruction by supporting contextualized assessment practices. It contributes by giving an in-depth account of non-test evaluation as a form of authentic assessment in Arabic language learning. Keyword: Authentic Assesment, Arabic Learning, Evaluation Model, Non-Test Evaluation, Student Competence.